Rainstorm and Flood Disasters: Case study of Shelter Management by Manila Municipal DRR (Disaster Risk Reduction) Teams during Tropical Storm Mario (Fung Wong) in 2014 - Estuar, Ma. Regina Justina E (Archīum Ateneo, 2015)
Floods are the leading cause of natural disaster-related deaths worldwide. This study aimed at assessing disaster preparedness and response by local Barangay (municipal) DRR (disaster risk reduction) teams during the flooding caused by tropical storm Mario in Manila in 2014. A cross-sectional and descriptive study was conducted, consisting of interviews in which five shelter managers participated. In total, 325 evacuees were received in 4 evacuation centers, whereas the remaining shelter received 30 families housed in tents. Only 3 shelters (60%) had some food and non-food items available prior to the arrival of evacuees. WASH (Water, sanitation and hygiene) services were insufficient; latrines were available in 4 (80%) shelters, but no latrine was available for displaced people housed in tents. Only 3 (60%) shelters had toilets cleaned regularly. Detergents, toothbrushes and toothpastes were provided in 3 (60 %) shelters, whereas only 2 (40%) had diapers for babies and none (0%) had hygienic period items for ladies. Food items were daily distributed in 3 (60%) shelters. Health services were not satisfactory, as medical consultations were organized but irregularly in 3 (60%) of the five shelters. Disaster preparedness and response in Barangay shelters were not satisfactory, suggesting the necessity for the central government to support local DRR volunteer teams. It is recommended to provide the volunteers with an inexpensive ICT (information and communications technology) tool to collect disaster preparedness data so that relief efforts will be more than sufficient at the time of disaster.